Zustreech or Encounters of a Transnational Kind: Negotiating Ukrainianness in Western Canada - Shostak, Natalia (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2003)
AbstractThis article deals with the questions of identity negotiation in a transnational context, through an ethnographic examination of contemporary “Ukrainian practices” in Mundare, a small Ukrainian community, located in the heart of the Ukrainian bloc settlement in east central Alberta. The article focuses on performative language and practices of a Zustreech cultural society organized in this community by recent immigrants from Ukraine. While identity negotiation between the local Ukrainians and their old country counterparts is fraught with miscommunication in the domain of various public events staged by the Zustreech society, such events do succeed in fostering new experiences of Ukrainian-Canadian identity.